Curriculum guide for teaching house officers and faculty: applying procedure codes effectively using chemical denervation as a model - Berri, Maryam; Beydoun, Noha; Johnson, Martha (Frontiers in Medicine, 2024)
Introduction The healthcare system in the United States relies heavily on physician-and house officer-driven initiation of billing and coding for collection of hospital payments and professional fees. Under the umbrella of practice management is the ever-changing and suboptimally taught concept of procedural billing and coding to house officers and faculty. Clinical providers and practitioners initiate billing and coding for performed services based on the procedural visit encounter, supported by the appropriate documentation. Correct charge capture is dependent on accurately linking CPT codes and J codes, including waste documentation, modifiers, and charge collection. We discuss a perspective regarding a new curricular methodology that teaches learners to apply an algorithmic approach for coding CPT codes, J codes, and modifiers for chemical denervation procedures involving high-cost botulinum toxin. We further recommend the use of visuals with algorithm development for other pertinent procedures that are specific to a department. Methods We developed a curriculum that includes algorithmic visuals, pre-and post-test questions, and reflections. It was implemented across various learner types. Results This chemical denervation curriculum was well-received and impactful in meeting the objectives of the course. It further expanded a learner’s vision of practice management that can be applied to other procedural examples. Discussion The results demonstrate a clear gap in practice management education, with pre-education knowledge on applying appropriate codes being particularly low among resident physicians. Learners found the algorithm we developed especially valuable, as it serves as a practical tool for accurately accounting for all aspects of CPT codes, modifiers, and J-codes. The methodology of the algorithmic approach proved to be innovative for avoiding billing write-offs and loopbacks that were beneficial for the training process. Learners indicated that this approach can be applied to other procedural billing.